SOCIOLINGUISTIC ANALYSIS OF BUSINESS DISCOURSE IN ENGLISH AND UZBEK LANGUAGES - Qodirova Mukaddas Tog‘ayevna (Western European Studies, 2024)
This article explores the sociolinguistic differences between English and Uzbek business discourses, focusing on formality, communication styles, and social priorities. English business discourse emphasizes competitiveness, technological innovations, and corporate structures, while Uzbek business discourse highlights social development, collective work, and rural entrepreneurship. Despite these differences, both discourses prioritize innovation and economic growth. The analysis is based on comparative methods, discourse analysis, and sociolinguistic approaches, offering insights into how business communication reflects cultural and social contexts
Keywords: Business discourse; sociolinguistics; innovation; competitiveness